Coupling of Transcription and Translation in Archaea: Cues From the Bacterial World - Weixlbaumer, Albert; Grünberger, Felix; Werner, Finn; Grohmann, Dina (Frontiers in Microbiology, 2021)
The lack of a nucleus is the defining cellular feature of bacteria and archaea. Consequently, transcription and translation are occurring in the same compartment, proceed simultaneously and likely in a coupled fashion. Recent cryo-electron microscopy and tomography data, also combined with crosslinking-mass spectrometry experiments, have uncovered detailed structural features of the coupling between a transcribing bacterial RNA polymerase (RNAP) and the trailing translating ribosome in Escherichia coli and Mycoplasma pneumoniae. Formation of this supercomplex, called expressome, is mediated by physical interactions between the RNAP-bound transcription elongation factors NusG and/or NusA and the ribosomal proteins including uS10. Based on the structural conservation of the RNAP core enzyme, the ribosome, and the universally conserved elongation factors Spt5 (NusG) and NusA, we discuss requirements and functional implications of transcription-translation coupling in archaea. We furthermore consider additional RNA-mediated and co-transcriptional processes that potentially influence expressome formation in archaea.